A Qualitative Study on Tertiary EFL Teachers’ Reflective Practices - Irma Amy Picauly; Listyani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Reflective practice is vital in English as a Foreign Language (EFL) education, facilitating transformative teaching and learning. This study addresses the research gap by exploring the types of reflective practices commonly used by eleven tertiary EFL teachers. The present study aims to investigate the types of reflective practice frequently employed by tertiary EFL teachers to enhance their professional development. Data collection involved a qualitative approach using questionnaires and semi-structured interviews with participants from a private university in Salatiga. The study identified a strong commitment to reflective practice among the participants, engaging in reflection-in-action, reflection-on-action, and reflection-for-action. Assessing students' attitudes, tailoring education to meet the individual needs of students, analyzing previous experiences for valuable insights and alternative approaches, and engaging in self-reflection to address instructional challenges are included in the three primary types of reflection. This study highlights the significance of reflective practices in nurturing teachers' professional growth and emphasizes the potential for ongoing improvement through self-awareness and self-assessment. Future research can further explore additional reflective teaching types and develop strategies to promote reflective practices among teachers.